Variations in product in reactions of naphthoquinone with primary amines - Singh, Marjit W.; Karmakar, Anirban; Barooah, Nilotpal; Baruah, Jubaraj B. (Beilstein Journal of Organic Chemistry, 2007)
Reaction of 1,2-naphthoquinone with primary amines gives a 2-amino-1,4-naphthoquinone derivative which is equivalent to 1,2 to 1,4 carbonyl transposition. For example the reaction of 1,2-naphthoquinone with 4-methoxyaniline gives 2-(4-methoxyanilino)-naphthoquinone-1,4-(4-methoxyanil) (1) and with n-butylamine gives 2-(butylamino)-naphthoquinone-1,4-butylimine (2) respectively. The compounds 1 and 2 are characterized by X-ray crystallography; they have hydrogen-bonded dimeric structures. Similar reaction of 1,4-naphthoquinone with 3-picolylamine and 4-picolylamine gives the corresponding 2-amino 1,4-naphthoquinones; two products are characterized by X-ray crystallography. The reaction of 1,4-naphthoquinone with 4-aminothiophenol and 1,4-naphthoquinone with 4-aminophenol are compared. The former leads to C-S and the latter to C-N bond formation. The reaction of 1,4-naphthoquinone with 4-aminothiophenol in an NMR tube is studied to explain that 2-(4-anilinothiolato) 1,4-naphthoquinone derivative to be the sole product in the reaction.